The mathematics of extinction across scales: from populations to the biosphere - Carlson,Colin; Burgio,Kevin; Dallas,Tad; Getz,Wayne (PeerJ Preprints, 2017)
The sixth mass extinction poses an unparalleled quantitative challenge to conservation biologists. Mathematicians and ecologists alike face the problem of developing models that can scale predictions of extinction rates from populations to the level of a species, or even to an entire ecosystem. We review some of the most basic stochastic and analytical methods of calculating extinction risk at different scales, including population viability analysis, stochastic metapopulation occupancy models, and the species area relationship. We also consider two major extensions of theory: the possibility of evolutionary rescue from extinction in a changing environment, and the posthumous assignment of an extinction date from sighting records. In the case of the latter, we provide a new example using data on Spix's macaw (Cyanopsitta spixii), the "rarest bird in the world," to demonstrate the challenges associated with extinction date research.
Keywords: extinction rates; extinction date estimation; species area relationship; population viability analysis; extinction risk; Spix's macaw; population modeling; metapopulation modeling